REINTERPRETATION OF THE KAFA’AH CONCEPT IN JASSER AUDA’S PERSPECTIVE - Wijaya, Sandy (Nurani, 2021)
This research is intended to study and analyze the concept of kafa'ah in JasserAuda's perspective. In the concept of kafa'ah, it should be noted that there are still many people who think that kafa'ah only includes the same elements in terms of degree or social strata or wealth. Whereas the essence of kafa'ah is not like that, but among the strategies to create a sakinah, mawaddah, warohmah family. This type of research is library research, namely by collecting a number of data related to the concept of kafa'ah in marriage according to JasserAuda's perspective with the approach maqashidasy-syariah. The Method analysis data used is an inductive qualitative method. This method is done by collecting data, compiled and classified into themes that will be presented, then analyzed and presented with a research framework and then given a full interpretation by describing what it is. The results of the study show that (1) Kafa'ah is equality or harmony, it is important to do in order to achieve the perfection of marriage that avoids domestic life from harm and misery; (2) Wisdom requireskafa'ah is to get to the marriage relationship sakinahmawaddahwarahmah,and result destination weddings are not only referring to the happiness of the world, but also happiness hereafter; (3) The essence of the requirement for kafa'ahinperspectiveJasserAuda's is as a form of self-protection and honor for both each partner and for the two families who have been united in a marriage bond. Keywords: Kafa'ah, Maqashid ash-Shari'ah, JasserAuda.